Was Domar right? Serfdom and factor endowments in Bohemia - Alexander Klein; Sheilagh C. Ogilvie (University of Kent, School of Economics, 2017)
Do factor endowments explain serfdom? Domar (1970) conjectured that high land-labor ratios caused serfdom by increasing incentives to coerce labor. But historical evidence is mixed and quantitative analyses are lacking. Using the Acemoglu-Wolitzky (2011) framework and controlling for political economy variables by studying a specific serf society, we analyze 11,349 Bohemian serf villages in 1757. The net effect of higher land-labor ratios was indeed to increase coercion. The effect greatly increased when animal labor was included, and diminished as land-labor ratios rose. Controlling for other variables, factor endowments significantly influenced serfdom. Institutions, we conclude, are shaped partly by economic fundamentals.
Keywords: J47; N33; O43; P48; 330; serfdom; land-labor ratio; institutions; labor coercion; rural-urban interaction